2009
DOI: 10.1186/1753-6561-3-s7-s29
|View full text |Cite
|
Sign up to set email alerts
|

Two-stage joint selection method to identify candidate markers from genome-wide association studies

Abstract: The interaction among multiple genes and environmental factors can affect an individual's susceptibility to disease. Some genes may not show strong marginal associations when they affect disease risk through interactions with other genes. As a result, these genes may not be identified by single-marker methods that are widely used in genome-wide association studies. To explore this possibility in real data, we carried out a two-stage model selection procedure of joint single-nucleotide polymorphism (SNP) analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 12 publications
(13 reference statements)
4
33
0
Order By: Relevance
“…The roles of variants in the PTPN22 gene on chromosome 1 were also confirmed by several of these studies. The three NARAC studies of Cho et al [2009], Niu et al [2009], and Wu et al [2009] used Stage 1 regression-based analysis (e.g., log-linear or logistic-regression models) to reduce the noise of non-significant SNPs, thereby limiting the number of SNPs analyzed in Stage 2. The results from these three Stage 1 studies contained statistically significant HLA-DRB1 variants, or chromosome 6 variants in regions that are in high LD with HLA-DRB1 variants.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The roles of variants in the PTPN22 gene on chromosome 1 were also confirmed by several of these studies. The three NARAC studies of Cho et al [2009], Niu et al [2009], and Wu et al [2009] used Stage 1 regression-based analysis (e.g., log-linear or logistic-regression models) to reduce the noise of non-significant SNPs, thereby limiting the number of SNPs analyzed in Stage 2. The results from these three Stage 1 studies contained statistically significant HLA-DRB1 variants, or chromosome 6 variants in regions that are in high LD with HLA-DRB1 variants.…”
Section: Resultsmentioning
confidence: 99%
“…The 26 windows were on chromosome 6 and were in high LD with HLA-DRB1 . Wu et al [2009] found 395 SNPs with significant marginal effect with Bonferroni p -value < 0.1, most of which were also on chromosome 6p21.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations